Is gene expression among women with rheumatoid arthritis dysregulated during a postpartum flare? - Matthew Wright; Mette K. Smed; J. Lee Nelson; Jørn Olsen; Merete L. Hetland; Vibeke Zoffmann; Damini Jawaheer (Arthritis Research & Therapy, 2021)
Abstract Background To evaluate our hypotheses that, when rheumatoid arthritis (RA) flares postpartum, gene expression patterns are altered compared to (a) healthy women, (b) RA women whose disease activity is low or in remission postpartum, and (c) pre-pregnancy expression profiles. Methods Twelve women with RA and five healthy women were included in this pilot study. RA disease activity and postpartum flare were assessed using the Clinical Disease Activity Index (CDAI). Total RNA from frozen whole blood was used for RNA sequencing. Differential gene expression within the same women (within-group) over time, i.e., postpartum vs. third trimester (T3) or pre-pregnancy (T0), were examined, using a significance threshold of q < 0.05 and fold-change ≥ 2. Results Nine of the women with RA experienced a flare postpartum (RAFlare), while three had low disease activity or were in remission (RANoFlare) during that time frame. Numerous immune-related genes were differentially expressed postpartum (vs. T3) during a flare. Fold-changes in expression from T3 to postpartum were mostly comparable between the RAFlare and healthy groups. At 3 months postpartum, compared to healthy women, several genes were significantly differentially expressed only among the RAFlare women, and not among the RANoFlare women. Some of these genes were among those whose “normal” expression was significantly modulated postpartum, and the postpartum expression patterns were significantly altered during the RA flare. There were also some genes that were significantly differentially expressed in RAFlare compared to both healthy and RANoFlare women, even though their expression was not significantly modulated postpartum. Furthermore, while postpartum expression profiles were similar to those at pre-pregnancy among healthy women, significant differences were found between those time points among the RAFlare women. Conclusions The large majority of gene expression changes between T3 and 3 months postpartum among RA women who flared postpartum reflected normal postpartum changes also seen among healthy women. Nonetheless, during a postpartum flare, a set of immune-related genes showed dysregulated expression compared to healthy women and women with RA whose disease activity was low or in remission during the same time frame, while other genes demonstrated significant differences in expression compared to RA pre-pregnancy levels.